Musculoskeletal disorders and work-related injuries among hospital day-and shift workers - D'Agostin, Flavia; Negro, Corrado (La Medicina del Lavoro, 2014)
Background: Most research findings show that shift-and night work are associated with cardiovascular, musculoskeletal and neurological disorders as well as work-related injuries among health care workers. Objectives: This sample based study on 246 hospital workers was performed to determine whether shift work may affect musculoskeletal disorders and injury risk. Methods: During the health surveillance program, data were collected by means of the Nordic questionnaire and the risk evaluation document. Results and conclusions: A sample of 134 shift workers was compared to a sample of 112 day workers. Hospital day workers were found  to be at greater risk of musculoskeletal symptoms in single or multiple body sites than shift workers. The prevalence of symptoms in the low back (63% vs 50%), neck (54% vs 42%) and upper extremities (26% vs 12%) was significantly higher in day workers than shift workers. In particular, among day nurses the prevalence of complaints in the upper extremities was more elevated (p